Factors associated with the knowledge and attitude of adolescents regarding male condom use - Vitória Caroline da Cunha Rodrigues; Gabriella Farias Lopes; Giovanna Evelyn Luna Silveira; Isabelle Barros Sousa; Marcela Matias Sena; Thays Silva de Souza Lopes; Priscila de Souza Aquino (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Identify factors associated with the knowledge and attitude regarding male condom use in school adolescents. Methods: Cross-sectional, quantitative, Knowledge, Attitude, and Practice survey, conducted with 114 adolescents from a public state high school from August to October 2017, in Fortaleza, Ceará, Brazil. Results: The assumption of having sufficient knowledge regarding safe sex, not having a casual/dating partner, and having had three or more sexual partners in the last three months affected adequate knowledge. Higher education of the mother and not talking to the mother about sex were factors that influenced the inappropriate attitude of the participants. Conclusion: The knowledge and attitude of adolescents are influenced both by their previous sexual relations and by their relationship with their mother and the level of her schooling. Thus, it is essential that health institutions promote actions aimed at sex education, with support from schools and health professionals in general.